STUDY OF MEDICATION ERRORS BY PROSPECTIVE OBSERVATIONAL APPROACH IN WARANGAL HOSPITALS - RAVULA, SHIVANI; JANGA, AKHILA; POONURU, RAJASEKHAR (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the study was to determine the prevalence of medication errors occurring in a multispecialty hospital in Warangal. Methods: A prospective observational study was conducted in Rohini Superspeciality Hospital, Hanamkonda, Warangal, from October 2018 to March 2019, to study the prevalence of medication errors. Results: In this study, 500 patients were selected, of which 160 were identified with medication errors. Two hundred and seventy-one medication errors were identified among these patients, of which 100 (60.63%) patients were male and 24.37% of patients were female. Conclusion: This present study manifests that medication errors were predominate in males than in females and also the common age group was 50–60 years.